Економічний ефект від впровадження подвійної колони комплексу КГК-200 - Дудля, М.А.; Вікторов, Г.М.; Кириченко, Г.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Economic benefit of introduction light-weight double column CLC-200 develops of economy due to reduction of metal consumption and cost of metal and reduction of budget cost of drilling of a chink.